The impact of immune dysfunction on perioperative complications in surgical COVID-19 patients: an imperative for early immunonutrition - Vincent P. Stahel; Samson D. Blum; Pratibha Anand (Patient Safety in Surgery, 2022)
Abstract Surgical patients with coronavirus disease 2019 (COVID-19) are vulnerable to increased perioperative complications and postoperative mortality, independent of the risk for contracting COVID-19 pneumonia after endotracheal intubation for general anesthesia. The presumed root cause of postoperative infections, microvascular soft tissue injuries and thromboembolic complications is largely attributed to the profound immune dysfunction induced by COVID-19 as a result of complement activation and the “cytokine storm”. The empirical therapy with anti-inflammatory agents has been shown to attenuate some of the adverse effects of systemic hyperinflammation in COVID-19 patients. In addition, the proactive concept of “immunonutrition” may represent a new promising avenue for mitigating the complex immune dysregulation in COVID-19 and thereby reduce the rates of surgical complications and postoperative mortality. This letter provides a narrative summary of the current state-of-the-art in the field of immunonutrition as it pertains to surgical patient safety in COVID-19 patients.